Clinical epidemiology in Italian Registry of Infective Endocarditis (RIEI): Focus on age, intravascular devices and enterococci. (1st July 2015) - Cecchi, Enrico; Chirillo, Fabio; Castiglione, Anna; Faggiano, Pompilio; Cecconi, Moreno; Moreo, Antonella; Cialfi, Alessandro; Rinaldi, Mauro; Del Ponte, Stefano; Squeri, Angelo; Corcione, Silvia; Canta, Francesca; et al.
Abstract: Introduction: The epidemiology of infective endocarditis (IE) is changing due to a number of factors, including aging and health related comorbidities and medical procedures. The aim of this study is to describe the main clinical, epidemiologic and etiologic changes of IE from a large database in Italy. Methods: We prospectively collected episodes of IE in 17 Italian centers from July 2007 to December 2010. Results: We enrolled 677 patients with definite IE, of which 24% health-care associated. Patients were male (73%) with a median age of 62 years (IQR: 49–74) and 61% had several comorbidities. One hundred and twenty-eight (19%) patients had prosthetic left side IE, 391 (58%) native left side IE, 94 (14%) device-related IE and 54 (8%) right side IE. A predisposing cardiopathy was present in 50%, while odontoiatric and non odontoiatric procedures were reported in 5% and 21% of patients respectively. Symptoms were usually atypical and precocious. The prevalent etiology was represented by Staphylococcus aureus (27%) followed by coagulase-negative staphylococci (CNS, 21%), Streptococcus viridans (15%) and enterococci (14%). CNS and enterococci were relatively more frequent in patients with intravascular devices and prosthesis and S. viridans in left native valve. Diagnosis was made by transthoracic and transesophageal echocardiography in 62% and 94% of cases, respectively. The in-hospital mortality was 14% and 1-year mortality was 21%. Conclusion: The epidemiology is changing in Italy, where IE more often affects older patients with comorbidities and intravascular devices, with an acute onset and including a high frequency of enterococci. There were few preceding odontoiatric procedures. Highlights: RIEI analyzed clinical epidemiology in 677 Italian patients with definite IE. IE in Italy has shifted to a more acute disease than previously described. IE affects older and more debilitated patients. IE is characterized by a high rate of staphylococcal and enterococcal, infections especially in IE on left prosthetic valve or cardiac device. A relevant medical problem is IE in patients with cardiac devices.